2012
DOI: 10.1021/jo301691h
|View full text |Cite
|
Sign up to set email alerts
|

Direct α-Arylation of α-Amino Carbonyl Compounds with Indoles Using Visible Light Photoredox Catalysis

Abstract: A general and mild method for the construction of functionalized 2-(1H-indol-3-yl)-2-amino-carbonyl compounds was achieved, which represents the first example of direct α-arylation of α-amino carbonyl compounds with indoles using the visible light photoredox catalysis strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(48 citation statements)
references
References 49 publications
1
42
0
3
Order By: Relevance
“…In the initial report by Stephenson, the resultant electrophilic iminium ions were trapped with nitroalkanes to deliver the corresponding α-functionalized products. This strategy has proven general for a wide range of nucleophilic coupling partners including malonates, 21 cyanide, 22 trifluoromethyl anion, 22 electron-rich aromatics, 23 and phosphonates 24 in addition to tethered amines and alcohols which forge the corresponding heterocycles via intramolecular cyclization 25 (Scheme 3). …”
Section: Amine α-Functionalizationmentioning
confidence: 99%
“…In the initial report by Stephenson, the resultant electrophilic iminium ions were trapped with nitroalkanes to deliver the corresponding α-functionalized products. This strategy has proven general for a wide range of nucleophilic coupling partners including malonates, 21 cyanide, 22 trifluoromethyl anion, 22 electron-rich aromatics, 23 and phosphonates 24 in addition to tethered amines and alcohols which forge the corresponding heterocycles via intramolecular cyclization 25 (Scheme 3). …”
Section: Amine α-Functionalizationmentioning
confidence: 99%
“…Photoredox catalysis has recently been emerged as a highly appealing alternative to the use of stoichiometric organic oxidants in the area of C–H functionalization. As a result, a photoredox‐catalyzed indolation of N ‐aryl‐glycine derivatives 1 was reported by the group of Li (Scheme ) . Ru(bpy) 3 Cl 2 ( PC1 ) was then used as photocatalyst with one atmosphere of oxygen as terminal oxidant to obtain the indole amino acid derivatives 23 in good yields.…”
Section: α‐C–h Functionalization At the Peptide Backbonementioning
confidence: 99%
“…However, efforts towards expanding the scope of amines have been recently reported. Li [82] and Rueping [83] independently reported that N -arylglycine derivatives 65 are viable substrates (Scheme 16). They are presumably converted to imines 65a that are intercepted by indoles to give the Mannich-like adducts 67 .…”
Section: Reviewmentioning
confidence: 99%